Republic of Slovenia : Technical Assistance Report-Contingency Planning and Crisis Management. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2016)
This Technical Assistance report makes recommendations regarding introduction of an effective framework for contingency planning and crisis management, including bank resolution and deposit guarantees, in Slovenia. It is recommended that a communication plan and strategy be developed, both within the Bank of Slovenia and at the national level, to speak with one voice during financial crises. The members of Co-ordination Group/Financial Stability Board (CG/FSB) must harmonize their efforts to carefully coordinate information, provide consistent communication to the public, and ensure that they use the same facts and assumptions. Whenever a crisis appears forthcoming, CG/FSB members should plan to deliver a media statement providing information in a constructive manner to reassure the public.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet